Pembuatan Peta Potensi Curah Hujan Dengan Menggunakan Citra Satelit Mtsat Di Pulau Jawa - Dian Ika Aryani; Bandi Sasmito; Arwan Putra Wijaya (Jurnal Geodesi UNDIP, 2014)
Rain that occurs anytime make rainfall information become needed. Rainfall information is one of the important information and needed by almost all fields. Moreover for Java isle, the most populous isle in Indonesia, and with all sorts of activities .     This study aims to make rainfall information in rainfall maps by utilizing geostationary meteorological satellite’s data, MTSAT-1R. The making of rainfall map created by the brightness temperature values is recorded in the infrared channel-1 (IR1) on MTSAT satellite imagery. MTSAT image data used starting on May 1, 2013 until August 31, 2013 as many as 2.931 data set.     Research methods include 1) conversing PGM data format to ERS one, 2) correcting geometric or doing registration on coordinate system, 3) incorporating data in every hour into daily, 4) converting digital value number to brightness temperature values, 5) grouping brightness temperatures values into rainfall classification, 6) layouting rainfall map using ArcGIS, 7) making rainfall map animations, and 8) making the websites     Results obtained in the form of rainfall map. To support the cloud movements and see the potential rainfall area, this study also create animated rainfall maps. Then, the results of rainfall maps are displayed on a website so public can utilize them.Keywords : Map, rainfall, Brightness temperature, MTSAT-1R, Website